Ferroptosis and its role in skeletal muscle diseases - Wang, Ying; Zhang, Zepeng; Jiao, Weikai; Wang, Yanyan; Wang, Xiuge; Zhao, Yunyun; Fan, Xuechun; Tian, Lulu; Li, Xiangyan; Mi, Jia (Frontiers in Molecular Biosciences, 2022)
Ferroptosis is characterized by the accumulation of iron and lipid peroxidation products, which regulates physiological and pathological processes in numerous organs and tissues. A growing body of research suggests that ferroptosis is a key causative factor in a variety of skeletal muscle diseases, including sarcopenia, rhabdomyolysis, rhabdomyosarcoma, and exhaustive exercise-induced fatigue. However, the relationship between ferroptosis and various skeletal muscle diseases has not been investigated systematically. This review's objective is to provide a comprehensive summary of the mechanisms and signaling factors that regulate ferroptosis, including lipid peroxidation, iron/heme, amino acid metabolism, and autophagy. In addition, we tease out the role of ferroptosis in the progression of different skeletal muscle diseases and ferroptosis as a potential target for the treatment of multiple skeletal muscle diseases. This review can provide a useful reference for the research on the pathogenesis of skeletal muscle diseases, as well as for clinical prevention and treatment.